Scandinavian Prospects for a Place-Based Randomized Experiment on Burglary Reduction - Sorensen, David W. M. (Journal of Scandinavian studies in criminology and crime prevention, 2007)
Despite their widespread implementation, there is a surprising absence of clear-cut, unambiguous evidence concerning the effectiveness of situational crime prevention approaches (e.g. alarms, neighborhood watch, property-marking) on residential burglary. This absence of evidence-which should not be confused with a presence of contradictory evidence-stems most notably from the fact that very few of the programs enacted to date have been evaluated under controlled, experimental conditions. The current article describes problems with previous evaluations and advocates the use of a place-based, randomized experimental design-which this author argues should be easier to implement in Scandinavia than elsewhere